Serum AMH in Physiology and Pathology of Male Gonads - Ewa Matuszczak; Adam Hermanowicz; Marta Komarowska; Wojciech Debek (International Journal of Endocrinology)
AMH is secreted by immature Sertoli cells (SC) and is responsible for the regression of Müllerian ducts in the male fetus as part of the sexual differentiation process. AMH is also involved in testicular development and function. AMHs are at their lowest levels in the first days after birth but increase after the first week, likely reflecting active SC proliferation. AMH rises rapidly in concentration in boys during the first month, reaching a peak level at about 6 months of age, and then slowly declines during childhood, falling to low levels in puberty. Basal and FSH-stimulated levels of AMH, might become a useful predictive marker of the spermatogenic response to gonadotropic treatment in young patients with hypogonadotropic hypogonadism. After puberty, AMH is released preferentially by the apical pole of the SC towards the lumen of the seminiferous tubules, resulting in higher concentrations in the seminal plasma than in the serum. Defects in AMH production and insensitivity to AMH due to receptor defects result in the persistent Müllerian duct syndrome. A measurable value of AMH in a boy with bilateral cryptorchidism is predictive of undescended testes, while an undetectable value is highly suggestive of anorchia or ovaries, as would be the case in girls with female pseudohermaphroditism and pure gonadal dysgenesis. Lower serum AMH concentrations in otherwise healthy boys with cryptorchidism, who were compared with their age-matched counterparts with palpable testes, have been reported previously. AMH levels are higher in prepubertal patients with varicocele than in controls. This altered serum profile of AMH in boys with varicoceles may indicate an early abnormality in the regulation of the seminiferous epithelial function. Serum AMH is known to be valuable in assessing gonadal function. As compared to testing involving the administration of human chorionic gonadotropin, the measurement of AMH is more sensitive and equally specific. Measurement of AMH is very useful in young children, because serum gonadotropin concentrations in those who are agonadal are nondiagnostic in midchildhood and serum testosterone concentrations may fail to increase with provocative testing in children with abdominal testes.